University-Industry Knowledge Transfer: Companies’ Perspective (Journal of Economic Research & Business Administration, 2015)
This paper reports the results of the study conducted in Almaty (Kazakhstan) on the attitudes of the representatives of firms towards knowledge transfer in telecommunications sector. A survey in the form of questionnaire was used as a method of the research. Overall, 28 telecommunications firms participated in the survey which constitutes to 54% response rate. The results of the study revealed positive attitudes of the representatives of telecommunications companies towards knowledge transfer as university-industry knowledge collaboration allows enterprises to engage in joint R&D with universities as well as to access highly qualified potential candidates for employment. According to telecommunications firms, the most important knowledge transfer channels are professional publications and reports, participation in conferences and seminars, and personal contacts. However, the study revealed a number of factors hindering the transfer of knowledge between universities and telecommunications companies. The main obstacle is the absence of any incentives by the government to encourage companies to engage in joint R&D with universities. This study is a pilot one and may serve as a good basis for future research in this area.
Keywords: knowledge transfer; university-industry collaboration; telecommunications sector; Kazakhstan